PERSEPSI AKUNTAN PUBLIK TERHADAP ISU-ISU YANG BERKAITAN DENGAN AKUNTAN PUBLIK PEREMPUAN - Astri Fitria; Lydia Setyawardani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
The purpose of this research is to analyze the perception among men and women in accountant public profession and also the s perception difference about women’s issues among them. The issues are chances for female accountant, treatment to female accountant, the acceptance to  female  accountant, commitment of female  accountant, and special accommodation for female accountant. The results of the field research show that there are no significant differences for all the issues. Between female or male accountant have fair perception that between female and male  accountant have equality in  chances, acceptance, commitment, and for the special accomodation. Both  also have the same oppinion that there are no sexual harassment and different treatment to female acountant.